What is compassion? A multicultural study on the semantic associations and subjective experiences of compassion - Matos, Marcela (2021)
Empirical research has documented the benefits of compassion for mental health, psychosocial and physiological wellbeing. Yet, definitions of compassion vary amongst theoretical approaches, researchers, clinicians and lay people. The meaning and nature of compassion can be misunderstood and become linked to fears, blocks and resistances to compassion. The current paper defines compassion from the perspective of compassion focused therapy (CFT) and distinguishes it from other commonly related concepts, using a qualitative methodological approach. Participants’ understanding of compassion was explored through their selection of the words they associated with compassion and self-compassion, and descriptions of recalled experiences of giving and receiving compassion, with cultural differences further examined. A sample of 584 adult participants was recruited from general community populations in Australia (n = 296), Portugal (n = 183) and Singapore (n = 105) and completed a self report questionnaire assessing the meaning and the subjective experiences of compassion. Empathy, Kindness and Understanding were the three words participants most frequently associated with ‘Compassion’. The most frequent three words selected by participants associated with ‘Self-compassion’ were Acceptance, Strength and Understanding. Various cultural differences among countries were identified and discussed. The findings also clarified participants’ experiences of compassion for others, receiving compassion from others and self-compassion, identified similarities and differences between countries, and revealed a significant proportion of people who were unable to recollect/ describe compassion experiences (across the three flows). The findings are discussed in light of a CFT framework and clinical implications for CFT practitioners are derived.